Little girls to advanced gymnasts: what can we learn from the surviving gymnasts? - Bradshaw, E. J.; Thomas, K. (ISBS Proceedings Archive (Michigan), 2019)
Talent identification programmes are widely employed in gymnastics to select young girls whom are thought to exhibit the pre-requisite traits to excel at the elite level in the future. This study revisits the Thomas, Wilson, and Bradshaw (2013) paper on 5-8 year old talent selected artistic gymnasts. The Gymnastics Victoria and Gymnastics Australia websites were data mined to track the competition history of these gymnasts. The original data (e.g. anthropometry, jump biomechanics) of the gymnasts that survived to an advanced level were compared against those whom did not, using the Kruskal Wallis test. The analysis revealed that better drop jump performance was the key indicator of longer term talent potential. Prospective analysis on surviving gymnasts provides better insights on the key attributes related to future advanced gymnastics potential.